Motivasi Belajar Siswa di Madrasah Aliyah Annur Nusa Kecamatan Kahu Kabupaten Bone - Reski, Mulia; Niswaty, Risma; Saleh, Sirajuddin (Jurnal Office, 2018)
This study aims to determine students' learning motivation in Madrasah Aliyah Annur Nusa, Kahu District, Bone Regency. This research is quantitative descriptive. The population of this study was 173 students and the number of samples was 44 students. Data collection techniques used are observation, questionnaires, interviews and documentation. Data analysis technique used is descriptive analysis. The results showed that students' learning motivation at Annur Nusa Madrasah Aliyah in Kahu sub-district, Bone Regency was high. Judging from their desires and desires, success is classified as very high, encouragement and needs in learning are high, expectations and ideals are very high, awards are high, interesting activities in learning are high and conducive learning environment is high.Â